2004
DOI: 10.1007/s00432-004-0652-x
|View full text |Cite
|
Sign up to set email alerts
|

New tumor necrosis factor-?-inducing protein released from Helicobacter pylori for gastric cancer progression

Abstract: Tipalpha is a new carcinogenic factor released from H. pylori mediated through NF-kappaB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(113 citation statements)
references
References 31 publications
5
107
1
Order By: Relevance
“…HP0596 homologues have not been detected in the genomes of related species (Campylobacter jejuni, Helicobacter hepaticus and Wiolinella succinogenes). The product of the hp0596 gene was named TNF-ainducing protein (Tip-a) by Suganuma's group [51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HP0596 homologues have not been detected in the genomes of related species (Campylobacter jejuni, Helicobacter hepaticus and Wiolinella succinogenes). The product of the hp0596 gene was named TNF-ainducing protein (Tip-a) by Suganuma's group [51].…”
Section: Resultsmentioning
confidence: 99%
“…We showed that Tip-a is involved in stimulation of macrophages as well as in colonization of mouse gastric mucosa. Analysis conducted by others also strongly documented that Tip-a (tumor necrosis factor [TNF] a-inducing protein) is a H. pylori carcinogenic factor involved in chemokine gene induction [28,51]. Although cell fractionation methods indicated localization of Tip-a in the inner membrane, the function of this protein implies surface exposition.…”
Section: Introductionmentioning
confidence: 99%
“…4,18,19) Since Tipa is incorporated into the cells not mediated through Type IV secretion system of H. pylori, Tipa is different from CagA or urease. We recently reported the direct interaction of Tipa with nucleolin on the cell surface of MGT-40 cells, although nucleolin is predominantly present in the nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Abbas et al (40) conducted on patients with liver cirrhosis observed no statistically significant difference in the levels of TNF-α expression when comparing positive and negative H. pylori groups, or groups with moderate and severe gastropathy (41). TNF-α is a key cytokine in tumor promotion; therefore, it is important to clarify how the pro-inflammatory cytokines induced by H. pylori are involved in the development of gastric cancer (42). Previous studies have demonstrated the presence of the gene encoder of the TNF-α inducer protein (Tipα) in the H. pylori genome, which functions as a carcinogenic factor by inducing the gene expression of TNF-α and activating NF-κB (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a key cytokine in tumor promotion; therefore, it is important to clarify how the pro-inflammatory cytokines induced by H. pylori are involved in the development of gastric cancer (42). Previous studies have demonstrated the presence of the gene encoder of the TNF-α inducer protein (Tipα) in the H. pylori genome, which functions as a carcinogenic factor by inducing the gene expression of TNF-α and activating NF-κB (41,42).…”
Section: Discussionmentioning
confidence: 99%